Sosialisasi Pemanfaatan dan Pembuatan Website Profil Sekolah di SDN Karangjambu 02 Kec. Balapulang Kab. Tegal - Ahillah, Ade Irma; Nurzaen, Satrio Bagus Putra; Nurhikmah, Rizki; Subekhi, Isriyana Nurus; Widiawati, Laili; Kusumo, Hanung Endro; Rosyidah, Agustina Fajriyatul; Laely, Nur; Juliyanti, Widya Rosi; Salsadila, Salma Selfi; Nurhadi, Ikhwan (Profetik: Jurnal Pengabdian Masyarakat, 2025)
The potential of technological resources is increasingly providing more benefits to users. One of them is website technology. The existence of a website is very important to support the delivery of intent and purpose through information media that can be accessed by the wider community. In addition, the website can also be used as a promotional media for a particular product. SDN Karangjambu 02 is one of the elementary schools in Karangjambu Village, Balapulang District, Tegal Regency that does not yet have a website media. Meanwhile, the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia (Kemendikbudristek) of the Republic of Indonesia has encouraged and provided guidance to schools in Indonesia to have a school profile website as part of an effort to increase transparency and accessibility of educational information. This study aims to create a school information system website at SDN Karangjambu 02. This school profile website media is considered important for conveying information about school activities to the community. And the most important thing is as a media for introducing schools or promotions to the community. The method used by the KKN student team from the Bakti Negara Islamic Institute (IBN) Tegal to socialize the use and creation of this website is data collection, concept design, website creation, implementation, and evaluation. The results obtained are in the form of a school website that can be accessed by the public at the address https://sdnkarangjambu02.sch.id The website displays school profile information (welcome, vision and mission, extracurricular activities, facilities), articles (activities at SDN Karangjambu 02), PPDB results (open quota, registration fees, registration requirements, and registration flow), information (announcements, agendas and achievements), contacts that can be contacted regarding information at SDN Karangjambu 02, Balapulang District, Tegal Regency.